Year of the Snake: An Analysis of the Polish Urban Legend of the Vistula Python - Napiórkowski, Mateusz (Lidé města, 2020)
Stories about wild and domesticated animals are among the most popular categories of urban legends. In modern folklore, they appear mysteriously, often following strange or scary happenings, like a quite recent tale, created in 2018, when the molted skin of a large snake (later identified as an Indian python) was found near the banks of the Vistula River in the suburbs of Warsaw. Owing to the extensive media coverage, the news spread quickly throughout Poland. For obvious reasons, people wondered where the snake was hiding. Several eyewitnesses, who could see the predator (or something that resembled it), wanted to give an account. Such animals then “disappear” forever but leave their mark on pop culture. The snake myth thus gave rise to numerous stand-up comedy acts, amateur music videos, and a comic book. This study analyses a number of such examples, obtained from the Internet. It also focuses on the mechanisms of the formation of urban legends, and their relation to fake news. One of the main questions of the article is therefore: why do these kinds of stories gain such wide popularity? Furthermore, the aim of the study is to analyse the reactions of Internet users to the news about the python. The topic was commented on by people with different world and political views, so it is worth considering whether the message about the python could play an important role in the integration of Polish society, or as a just another platform for the exchange of thoughts.